Camel contagious ecthyma : Risks in young calves - A.I. Khalafalla (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2000)
Camels are important animals uniquely adapted to dry and arid environment. High calf mortality appears to be one of the major constraints to optimum productivity in camels. Camel contagious ecthyma (CCE) is a sparsely studied disease caused by a Parapox genus virus of the Poxviridae family. In Sudan, about 98% of CCE cases occur in calves less than one year old with 60-100% morbidity and 9-38% mortality rates. The disease is endemic in most parts of Sudan where camels are raised with variations in intensity of infection and mortality rates. The disease reappears regularly every year in the early rainy season (July-August) affecting camel calves in their first autumn of grazing. CCE lesions are confined to the head, in particular to the lips, nostrils and eyes, without becoming generalized. These lesions are characterized by a distinctive feature, i.e. the appearance of fissured crusts that clinically differentiate the disease from camel pox or papillomatosis. The disease affects the growth rate of camel calves by interfering with their ability to suckle or graze. The economic impact of this poorly studied disease is discussed. CCE needs to be seriously considered as one of the factors that affect camel productivity in Sudan.